KAJIAN EKSPERIMENTAL ALATMULTI FUNGSI BERCATU DAYA TERMOELEKTRIKUNTUK PENDINGINAN DAN PEMANASAN - Dian Wahyu; Andriyanto Andriyanto; Hanif Hanif; Rino Sukma; Yazmendra Rosa (ROTOR, 2016)
The versatile tool from thermoelectric power supply has been made and has satisfied performance. The selection of material and tool is chosen based on the product availability in the market and the cooling device is selected based on the number of cooling load. Thermoelectric cooler is one of the electrical components that transfer a heat to another side by electric discharge. Cold temperature generated in the cold side is used to cooling the working fluid and the heat temperature is used to heating the water. The water is used as cooling fluid and used as much as 3L to cooling the room temperature where it is integrated by fan to either accelerate the heat absorption process or dispose the heat. Small heat exchanger is used to expand the heat absorption area in a cooling room. The results show that cooling element is capable to work constantly on the cooling power for one element by 37 W. Meanwhile in the tool characteristics, it is capable to produce low temperature of 13°C that begins in 40th minute. In addition, warm water temperature with volume of 30L is capable to produce 45°C. The maximum efficiency from cooling device is occurred when the different temperature in both side is nearly minimum. Coefficient of performance (COP) of cooling system is obtained at 0,58. Keywords: thermoelectric, cooling room system, COP (coefficient of performance)